ACTUALIZATION OF RELIGIOUS EDUCATION AND SCIENCE IN EDUCATING THE CHARACTER OF LEARNERS IN SCHOOLS AND MADRASAHS - Rahayu, Suci Nur; Farihah, Umi; Suhardi, Andi (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
Character education has become the main focus in education to build a generation that is not only intellectually intelligent but also has high morality. This article discusses the synergy between religious and science education in developing students' character in schools and madrasahs. Religious education provides a moral and spiritual foundation, while science trains the ability to think critically and understand natural phenomena logically. By integrating the two, learners are expected to have strong characters that include ethics, empathy, responsibility, and love for science. This research uses a qualitative approach with a literature study method to explore the relevance of actualizing both fields in character education. The findings show that integrating religion and science effectively can encourage learners to become individuals with integrity, innovative, and adaptive to global challenges.